Kondisi Kesejahteraan Petani Padi Sawah Di Kecamatan Bayang Kabupaten Pesisir Selatan - Oktavia, Risa; Rianto, Slamet; Farida, Farida (Pendidikan Geografi, 2013)
This study aims to determine the condition of the welfare of rice farmers in the district of Bayang ni the districts of Pesisir Selatan in the ability to meet family needs. This research is descriptive. The population in this study is a family rice farmers in 2191 as farmers, sampling techniques in the study area is purposive sampling based on the highest number of rice farmers in the region with a total population sample was 532 farmers, while the respondent sampling technique is random sampling with proportional proportion of 10% of the total sample of respondents 51 farmers. Research data collection using questionnaires with data analysis using the percentage formula. These results indicate that: 1) the ability of rice farmers families in meeting the conditions of the board (housing) is good with a percentage of 65.83%. 2) the ability of rice farmers families in finding the level of income is relatively less with the percentage of 39.22%. 3) the ability of rice farmers families in achieving health needs is quite enough with the percentage of 49.58%. 4) the ability of rice farmers families in achieving education in the junior high school level is quite the percentage of 49.58%. This means that the condition of the welfare of the family rice farmers in the district of Pesisir Selatan districts Bayang Belonging to the family prosperous III where the family has been able to meet the overall needs of basic, social, psychological and family development but have not been able to regularly contribute to Public.